2016
DOI: 10.1186/s13613-016-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

Runtime and aPTT predict venous thrombosis and thromboembolism in patients on extracorporeal membrane oxygenation: a retrospective analysis

Abstract: Background Even though bleeding and thromboembolic events are major complications of extracorporeal membrane oxygenation (ECMO), data on the incidence of venous thrombosis (VT) and thromboembolism (VTE) under ECMO are scarce. This study analyzes the incidence and predictors of VTE in patients treated with ECMO due to respiratory failure.MethodsRetrospective analysis of patients treated on ECMO in our center from 04/2010 to 11/2015. Patients with thromboembolic events prior to admission were excluded. Diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 23 publications
(25 reference statements)
4
26
1
Order By: Relevance
“…Vice versa, patients with aPTT values below the targeted therapeutic range did not necessarily develop thromboembolic events. However, practically all the thromboembolic events occurred when minimal aPTT values were below 50 s. This is in line with Trudzinski et al, who found an aPTT level below 50 s to be predictive for thromboembolism in ARDS patients under ECMO [ 25 ]. On the other hand, almost all bleeding events occurred when the maximal aPTT of the patients was above 50–60 s. Strikingly, more than two-thirds of all bleeding events were associated with maximum aPTT values above 75 s. Although these results only reflect the population of this study, we propose that this aPTT value could be regarded as the utmost tolerable upper limit under extracorporeal lung support to avoid hemorrhage.…”
Section: Discussionsupporting
confidence: 77%
“…Vice versa, patients with aPTT values below the targeted therapeutic range did not necessarily develop thromboembolic events. However, practically all the thromboembolic events occurred when minimal aPTT values were below 50 s. This is in line with Trudzinski et al, who found an aPTT level below 50 s to be predictive for thromboembolism in ARDS patients under ECMO [ 25 ]. On the other hand, almost all bleeding events occurred when the maximal aPTT of the patients was above 50–60 s. Strikingly, more than two-thirds of all bleeding events were associated with maximum aPTT values above 75 s. Although these results only reflect the population of this study, we propose that this aPTT value could be regarded as the utmost tolerable upper limit under extracorporeal lung support to avoid hemorrhage.…”
Section: Discussionsupporting
confidence: 77%
“…This was due to differences in timing of ECMO (Table ), as preoperative ECMO therapy (ie, bridge‐to‐transplant) was associated with longer ECMO durations while waiting for a compatible organ. The runtime of ECMO therapy is a well described factor in the probability of complications, including thromboembolic events . Therefore, we decided to perform post hoc corrections for these relevant baseline differences between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study, Trudzinski et al . 3 reported an incidence of 46.1% for venous thrombosis and/or thromboembolism in patients treated on ECMO with systemic anticoagulation.…”
Section: Introductionmentioning
confidence: 99%